Annual itinerant teacher training program for Negro trade and industrial teachers of Florida - Thomas, Maxwell S., author; Hinderman, Roy Aaron, 1900-, advisor; Heilig, Herb, committee member; Marshall, T. O., committee member (Colorado State University. Libraries, 1945)
To view the abstract, please see the full text of the document.
Keywords: Education -- Florida; African Americans -- Education